Individual actors in community theater: Implications for sense of community. Issue 4 (7th August 2020) - Forenza, Brad; Tredinnick, Lorin
ABSTRACT: Throughout history, theater and the arts have been mediums to bond individuals and advance social change. Community theater has the added benefit of allowing nonprofessional thespians the opportunity to collaborate with each other, in pursuit of common goals, while advancing local capacity and individual wellbeing. To the extent that community theaters provide voluntary participants with a civic space to harness intrinsic passions, participation may function as a form of primary prevention against negative health and mental health outcomes at the individual level. To this end, the present study utilizes a Sense of Community framework and in-depth interviews with 14 participants to discern the ways in which community theater might be able to facilitate social inclusion and community development. Findings support and extend our understanding of extant Sense of Community dimensions. Implications for policy, practice, and future research are also discussed.